Genetic investigations of sudden unexpected deaths in infancy using next-generation sequencing of 100 genes associated with cardiac diseases - Hertz, Christin Loeth (Eur J Hum Genet, 2016)
Sudden infant death syndrome (SIDS) is the most frequent manner of post-perinatal death among infants. One of the suggested causes of the syndrome is inherited cardiac diseases, mainly channelopathies, that can trigger arrhythmias and sudden death. The purpose of this study was to investigate cases of sudden unexpected death in infancy (SUDI) for potential causative variants in 100 cardiac-associated genes. We investigated 47 SUDI cases of which 38 had previously been screened for variants in RYR2, KCNQ1, KCNH2 and SCN5A. Using the Haloplex Target Enrichment System (Agilent) and next-generation sequencing (NGS), the coding regions of 100 genes associated with inherited channelopathies and cardiomyopathies were captured and sequenced on the Illumina MiSeq platform. Sixteen (34%) of the SUDI cases had variants with likely functional effects, based on conservation, computational prediction and allele frequency, in one or more of the genes screened. The possible effects of the variants were not verified with family or functional studies. Eight (17%) of the SUDI cases had variants in genes affecting ion channel functions. The remaining eight cases had variants in genes associated with cardiomyopathies. In total, one third of the SUDI victims in a forensic setting had variants with likely functional effect that presumably contributed to the cause of death. The results support the assumption that channelopathies are important causes of SUDI. Thus, analysis of genes associated with cardiac diseases in SUDI victims is important in the forensic setting and a valuable supplement to the clinical investigation in all cases of sudden death.